Peran Pembimbing Kemasyarakatan dalam Mendampingi Anak yang Berhadapan dengan Hukum - Yusri Yusri; Rispawati Rispawati; Yuliatin Yuliatin (MANAZHIM, 2022)
Community Supervisor according to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) in Article 1 paragraph (13) is a functional law enforcement official who carries out community research, guidance, supervision, and assistance to children in and outside the criminal justice process. This research aims to find out the role of Community Supervisors in assisting Children Who Face The Law at the Correctional Center Klas II Mataram. This research uses a qualitative approach with descriptive methods. The subject in this study is the Community Supervisor. Data collection techniques use observation techniques, interviews, and documentation. Based on the results of the study shows that the Community Supervisor in assisting children who face the law consists of assistance at the investigation stage, the prosecution stage, the trial stage, and the trial. The internal factors that affect the Community Supervisor in assisting children who face the law are Human Resources, the area of work area, and the budget of funds. While external factors consist of cooperative relations with other agencies and coordination with parents / guardians and the community.